Symposium 4: Exploring the context for professional development in a large distance university - Poniatowska, Barbara (Proceedings of the International Conference on Networked Learning, 2010)
This paper illustrates the significance of distributed working in influencing the needs and relevance of professional development in a large distance university. It describes the particular context and challenges for staff who work at the Open University (UK), and the distinctive ways in which staff work together within that environment. This has direct implications for the opportunities for and success of professional development, whether that is formal provision or whether it takes place informally, on the job. With a rapidly increasingly pace of change there is a pressing need to keep staff regularly updated with new working practices in learning and teaching. At the same time, the demands of delivering education at scale places specific demands on its staff, who work in ways which may be unfamiliar to traditional campus based institutions. The picture is of an institution where all staff need to make use of technologies in their working practices as a requirement of the job. The extent to which they embrace these technologies and their attitudes to its adoption varies according to their context and circumstances. The adoption of technologies into the working practices of staff has been a gradual process over the last decade, driven in part by the needs of particular modules, but also by University strategy, and probably for those who work at home by trends in domestic use of technologies. A wide range of modules and other resources are in place to support professional development, alongside the informal development which takes place in a complex web of working communities. We have illustrated how staff at the OU belong to a large number of working communities, some of them short term, others which may last for several years. Critically, many of these communities consist of staff with varied roles and responsibilities who may be academic, or academic-related, full or part-time who are united in a common goal and may have common needs for development. Staff may commonly belong to several communities at one time, for example they might belong to module teams but also have connections with a particular unit, or to a region or nation, sometimes with conflicting loyalties or perspectives. Finally, it is common for members of these communities to be geographically dispersed, so communication technologies have a central role in supporting and sustaining their effectiveness and viability.